METAPHORICAL LEXICON IN MAENA LYRICS OF WEDDING IN NIAS: ECOLINGUISTICS STUDY - Mastawati Ndruru; Mirsa Umiyati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
ABSTRACT This research is about language phenomena realized in Nias language. The title is â€œâ€Metaphorical Lexicon in Maena Lyrics of Wedding in Nias: Ecolinguistics Studyâ€. Grammatical category of metaphorical lexicon and dimensionality of the social praxis realized in Maena lyrics of wedding Nias are the objectives of the research. Data of the research are obtained from Maena video in Nias language and then are transcribed into written form. There are two types of required data, such as metaphorical biotic lexicon and abiotic lexicon. Observation and taking note technique were employed in collecting the data. The data were analyzed by orienting dialectical ecolinnguistic theory of Bang and DÃ¸Ã¸r. The result of the analysis were displayed in formal and informal methods. The result shows that there are two findings, namely (1) grammatical category of metaphorical lexicon realized in Maena lyrics of wedding are biotic ecology, such as mbala (papaya) and gae (banana) and abiotic ecology, such as teâ€™u (mice), and mao (cat). (2) social praxis dimension of metaphorical lexicon realized in Maena lyrics of wedding in Nias are biological dimension as indicated in the use of natural lexicon in the lyrics, idelogical as indicated in the concept formed as genuine meaning communicated through Maena lyrics, and sociological dimension as indicated through conceptual deliverance in Maena lyrics. Keywords: maena lyrics of wedding, grammatical category, social praxis dimension